Análise de programa de guarda parque: construção de uma proposta para Manaus - Chagas, Denis Sena das (Instituto Nacional de Pesquisas da Amazônia - INPA, 2013)
As the first protect areas or conservation units were established in the Word, as a means to safeguard wildlife on Earth, it also appears the Park Ranger or Forest Guard, the main character responsible for the areas protection. He is a Professional exclusive to the protected areas, with special attributes, work routine and a diversified acting form different from any other professional category. This study objective is to establish the technical and legal basis to propose the creation and framework of a Forest Guard career for the Manaus municipality to secure its protected areas. The work describes and proposes technical and legal instruments adequate for the implementation of this career, based on positive and negative experiences obtained from similar institutions from other parts of Brazil and abroad. Twelve Brazilian states have protection and surveillance programs for their protected areas, and only three had legally established park guard programs. In five countries also included in the study (Argentina, Spain, Cuba, United States and Costa Rica), the career already exists created by federal regulation. Legal instruments of program creation for the studied states and countries were analyzed for their organization framework and guard’s selection process, educational level, training and remuneration. The largest difficulty for data gathering was the dispersed and varied nature of the information found in norms and regulations, and not always representing the observed in loco field data. We observed a diversity of attributions, large variation on educational level required by different programs, and insufficient training to prepare the hired professionals to all activities inherent to the position. The number of park guards identified in each studied state was much lower than expected, given the extension of the country’s protected areas. Wages received by those professionals were highly variable, and in general incompatible with their responsibilities. Nonetheless, the documents evaluated were enough to support the formulation of a proposal for a legal norm creating a park guard program for Manaus protected areas.
Keywords: Unidades de conservação; Guarda parque; Áreas protegidas